In vitro anti- biofilm and anti-bacterial activity of Sesbania grandiflora extract against Staphylococcus aureus - Arumugam Dhanesh Gandhi; Dhandapani Kayal Vizhi; Kubendiran Lavanya; V.N. Kalpana; V. Devi Rajeswari; Ranganathan Babujanarthanam (Biochemistry and Biophysics Reports, 2017)
The main objective of this research is to investigate the anti-biofilm and anti-bacterial activity of Sesbania grandiflora (S. grandiflora) against Staphylococcus aureus. S. grandiflora extract were prepared and analyzed with UV –Vis spectroscopy, Fourier transform infrared spectroscopy, Dynamic light scattering. Biofilm forming pathogens were identified by congo-red assay. Quantification of Extracellular polymeric substance (EPS) particularly protein and carbohydrate were calculated. The efficacy of the herbal extract S. grandiflora and its inhibition against the pathogenic strain of S. aureus was also evaluated. The gradual decrease or disappearance of peaks reveals the reduction of protein and carbohydrate content in the EPS of S. aureus when treated with S. grandiflora. The antibacterial activity of S. grandiflora extract against the bacterial strain S. aureus showed that the extract were more active against the strain. To conclude, anti-biofilm and antibacterial efficacy of S. grandiflora plays a vital role over biofilm producing pathogens and act as a good source for controlling the microbial population.